2010
DOI: 10.1098/rspb.2010.0877
|View full text |Cite
|
Sign up to set email alerts
|

Diet and hormonal manipulation reveal cryptic genetic variation: implications for the evolution of novel feeding strategies

Abstract: When experiencing resource competition or abrupt environmental change, animals often must transition rapidly from an ancestral diet to a novel, derived diet. Yet, little is known about the proximate mechanisms that mediate such rapid evolutionary transitions. Here, we investigated the role of diet-induced, cryptic genetic variation in facilitating the evolution of novel resource-use traits that are associated with a new feeding strategy-carnivory-in tadpoles of spadefoot toads (genus Spea). We specifically ask… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(75 citation statements)
references
References 60 publications
(59 reference statements)
3
72
0
Order By: Relevance
“…Whereas the previous examples demonstrate CGV by the transformation of invariant into variant (and often aberrant) phenotypes, estimating V A allows the possibility of phenotypic variation before perturbation as well. Several recent studies have demonstrated that ecologically relevant changes to environment can increase V A in natural populations, including body size in sticklebacks 28 , spermathecae number in dung flies 29 , plasma antioxidant level in gulls 30 , and traits associated with facultative carnivory in spadefoot toad relatives 31 .…”
Section: What Does Cgv Look Like?mentioning
confidence: 99%
“…Whereas the previous examples demonstrate CGV by the transformation of invariant into variant (and often aberrant) phenotypes, estimating V A allows the possibility of phenotypic variation before perturbation as well. Several recent studies have demonstrated that ecologically relevant changes to environment can increase V A in natural populations, including body size in sticklebacks 28 , spermathecae number in dung flies 29 , plasma antioxidant level in gulls 30 , and traits associated with facultative carnivory in spadefoot toad relatives 31 .…”
Section: What Does Cgv Look Like?mentioning
confidence: 99%
“…Partially beneficial plastic responses may permit some genotypes faced with a change in environment to persist, and so provide opportunities for subsequent evolution [5,10,29,30]. Plasticity may also reveal genetic variation under extraordinary or novel conditions that can be acted on by selection [22,29,31,32]; variation that is otherwise hidden in the population under its standard conditions [33][34][35]. When heritable variation in environmentally induced responses influences fitness, then any genetic variation in the form of the plastic response may provide an axis of variation on which selection can act.…”
Section: Introductionmentioning
confidence: 99%
“…When confronted with a novel, stressful environment, epigenetic mechanisms enable organisms to generate new phenotypic variants rapidly through phenotypic plasticity [63]; this process increases the likelihood that at least some individuals will survive the stressful situation [64][65][66] (Figure 1b).…”
Section: How Epigenetic Inheritance May Facilitate Diversification Anmentioning
confidence: 99%